2014
DOI: 10.1038/cdd.2014.68
|View full text |Cite
|
Sign up to set email alerts
|

Lipocalin 2 modulates the cellular response to amyloid beta

Abstract: The production, accumulation and aggregation of amyloid beta (Ab) peptides in Alzheimer's disease (AD) are influenced by different modulators. Among these are iron and iron-related proteins, given their ability to modulate the expression of the amyloid precursor protein and to drive Ab aggregation. Herein, we describe that lipocalin 2 (LCN2), a mammalian acute-phase protein involved in iron homeostasis, is highly produced in response to Ab 1-42 by choroid plexus epithelial cells and astrocytes, but not by micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
88
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(91 citation statements)
references
References 55 publications
2
88
0
1
Order By: Relevance
“…Robust increased NGAL protein levels were found in AD post-mortem human brain tissue [184], a mouse model for MS [186], and mouse model for cerebral ischemia [187]. Increased NGAL protein levels are detrimental to neuronal health [188] and sensitize neurons and other brain cell types to cell death upon exposure to Aβ and oxidative stress [184,189,190]. In addition, NGAL was shown to further promote pro-inflammatory reactions, and to stimulate classical inflammatory activation of microglia and astrocytes [191,192].…”
Section: Tnfr1-possible Downstream Targets In Neurodegenerationmentioning
confidence: 99%
“…Robust increased NGAL protein levels were found in AD post-mortem human brain tissue [184], a mouse model for MS [186], and mouse model for cerebral ischemia [187]. Increased NGAL protein levels are detrimental to neuronal health [188] and sensitize neurons and other brain cell types to cell death upon exposure to Aβ and oxidative stress [184,189,190]. In addition, NGAL was shown to further promote pro-inflammatory reactions, and to stimulate classical inflammatory activation of microglia and astrocytes [191,192].…”
Section: Tnfr1-possible Downstream Targets In Neurodegenerationmentioning
confidence: 99%
“…Altogether, these might aggravate the pro-inflammatory profile and overall CNS pathology in AD (Medeiros and LaFerla, 2013;Sofroniew and Vinters, 2010). Of note, as referred before, LCN2 was shown to be overproduced also by astrocytes, in vitro, in response to Aβ peptides (Mesquita et al, 2014) and to be increased in the brain of AD patients (Naude et al, 2012). Moreover, it was recently shown that increased levels of LCN2…”
Section: Microgliamentioning
confidence: 93%
“…of AD. Of note, it was shown that AD patients present altered levels of LCN2 in the CSF (Naude et al, 2012), and that LCN2 is involved in the in vitro pro-inflammatory response to increased level of Aβ peptides, displaying a detrimental effect on brain cell survival (Mesquita et al, 2014). Considering this new evidence, it will be important to further elucidate the role of LCN2 in the context of an in vivo model of AD.…”
Section: The Inflammatory Response At the Bbbmentioning
confidence: 96%
See 2 more Smart Citations